(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
Mixed-language PR posts are increasingly common in institutional digital communication, yet their pragmatic purpose is not always “natural bilingualism.” This thesis examines the tension between translanguaging as meaning-making and branding as strategic language display in English- and Uzbek-context PR posts. Using a qualitative pragmatic-discourse approach, the study analyzes publicly available posts from Uzbek institutional/large-service Telegram channels and English-language institutional social media pages where mixed-language captions occur. The analysis focuses on pragmatic functions of language alternation: attention capture, authority softening, inclusivity cues, credibility borrowing, procedural clarity, and commercial persuasion. Uzbek digital PR shows frequent alternation among Uzbek–Russian–English lexical tokens (e.g., cashback, bonus) to maximize reach in a Telegram-dominant ecosystem (UzDaily, 2025). Findings argue that mixed-language PR operates on a continuum: at one end, translanguaging (audience-oriented repertoire use); at the other, branding (curated multilingual identity). The study contributes a functional model explaining when language mixing signals solidarity and accessibility versus prestige and market positioning.